Restructuring Legal and Human Rights Curriculum: Anti-Bullying Dissemination Study in Junior High Schools - Ahmad Arifin; Nur Syahidah Dharmawan, Syifa; Kania, Dede (VARIA HUKUM, 2025)
Abstract: This research aims to explore the urgency and strategy of structuring the legal and human rights awareness curriculum through an anti-bullying dissemination study at the junior high school level. The formulation of the problem raised is how the urgency of developing a legal and human rights awareness curriculum and structuring efforts to increase students' understanding and awareness of legal and human rights issues, especially in the context of bullying prevention. The research method used an extension approach through stages that included needs assessment, interactive seminars, discussions, case simulations, and interpersonal skills training. The results showed that the implementation of a law and human rights-based curriculum had a significant impact in reducing cases of bullying, increasing empathy, and building a culture of respect for human rights in the educational environment. These findings emphasize the importance of integrating the values of law and human rights in the formal education system to create a young generation that is aware of the law, has character, and has a culture of peace.